2016
DOI: 10.1038/ncomms11248
|View full text |Cite
|
Sign up to set email alerts
|

Steroid binding to Autotaxin links bile salts and lysophosphatidic acid signalling

Abstract: Autotaxin (ATX) generates the lipid mediator lysophosphatidic acid (LPA). ATX-LPA signalling is involved in multiple biological and pathophysiological processes, including vasculogenesis, fibrosis, cholestatic pruritus and tumour progression. ATX has a tripartite active site, combining a hydrophilic groove, a hydrophobic lipid-binding pocket and a tunnel of unclear function. We present crystal structures of rat ATX bound to 7α-hydroxycholesterol and the bile salt tauroursodeoxycholate (TUDCA), showing how the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
103
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 76 publications
(105 citation statements)
references
References 48 publications
2
103
0
Order By: Relevance
“…The most likely candidate for an LPA allosteric binding site is the ATX tunnel, which has been shown to bind natural steroids 16 and, importantly, has also been suggested to bind LPA in a series of crystal structures reported in 11 ; where the authors showed density for about six carbons of the acyl chain of LPA, bound to the tunnel. Aiming to confirm this interaction, we designed a series of biochemical assays studying the modulation of ATX enzymatic activity by LPA in the presence of different well-characterized inhibitors that bind in the orthosteric and allosteric sites.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The most likely candidate for an LPA allosteric binding site is the ATX tunnel, which has been shown to bind natural steroids 16 and, importantly, has also been suggested to bind LPA in a series of crystal structures reported in 11 ; where the authors showed density for about six carbons of the acyl chain of LPA, bound to the tunnel. Aiming to confirm this interaction, we designed a series of biochemical assays studying the modulation of ATX enzymatic activity by LPA in the presence of different well-characterized inhibitors that bind in the orthosteric and allosteric sites.…”
Section: Resultsmentioning
confidence: 99%
“…The first of these inhibitors was the bile salt TUDCA, an inhibitor with IC 50 of 11 µM, which we previously reported to bind the allosteric site 16 . The effect of LPA activation under conditions where ATX is partially inhibited by three TUDCA concentrations was measured.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations